2003
DOI: 10.1046/j.0931-1793.2003.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Salmonella spp. in Pet Mammals, Reptiles, Fish Aquarium Water, and Birds in Trinidad

Abstract: The prevalence of Salmonella spp. was determined in 970 animals comprising 423 pet birds, 485 fish aquaria water and 62 other pets (40 pet mammals, 14 reptiles, eight others - crustaceans, snail, stingray) from both pet shops and households throughout Trinidad. The serotypes of Salmonella spp. isolated were identified and the resistance to various antimicrobial agents was determined. Overall nine (0.9%) of 970 pet animals were positive for Salmonella spp. Six isolates of Salmonella spp. were recovered from all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 19 publications
2
30
1
Order By: Relevance
“…The highest level of resistance in this study was observed for streptomycin (7.7%). Resistance to this antibiotic in Salmonella strains derived from reptiles was noted by a number of other authors (Seepersadsingh and Adesiyun 2003;Chen et al 2010;Barazorda Romero et al 2015;Bertelloni et al 2016). A low prevalence of tetracycline resistance was detected in this study (2.6%), which is in agreement with published results (Ebani et al 2005;Sylvester et al 2014).…”
Section: Eublepharis Maculariussupporting
confidence: 82%
“…The highest level of resistance in this study was observed for streptomycin (7.7%). Resistance to this antibiotic in Salmonella strains derived from reptiles was noted by a number of other authors (Seepersadsingh and Adesiyun 2003;Chen et al 2010;Barazorda Romero et al 2015;Bertelloni et al 2016). A low prevalence of tetracycline resistance was detected in this study (2.6%), which is in agreement with published results (Ebani et al 2005;Sylvester et al 2014).…”
Section: Eublepharis Maculariussupporting
confidence: 82%
“…IV was found to be common in iguana lizards (de Sá & Solari, 2001;Pfleger et al, 2003). Serovar Typhimurium and Enteritidis were rarely detected from reptiles (Warwick et al, 2001;Seepersadsingh & Adesiyun, 2003), nevertheless, the carriage of other human-associated salmonellae serovars, particularly multidrug-resistant strains usually occur without obvious symptoms of diarrhea, thus salmonellae seem to be essentially normal component of reptilian intestinal flora (Warwick et al, 2001;Ebani et al, 2005). Cases of reptile-associated human salmonellosis were reported in the United States, Canada and Europe since the 1960's (Weinstein et al, 1995;Woodward et al, 1997;Olsen et al, 2001;Warwick et al, 2001).…”
Section: Domestic and Wild Animalsmentioning
confidence: 99%
“…Unfortunately, these suggestions were not taken well into consideration in many parts of the world and as a result, different serovars of salmonellae have acquired multipledrug resistance and became ubiquitous in the environment. Various salmonellae serovars resistant to wide range of antimicrobial drugs were isolated from the faeces of diseased and apparently healthy livestock and poultry (Ahmed et al, 2009), food (dairy products; meat; poultry products) (Antunes et al, 2003;Zhao et al, 2003;Dallal et al, 2010), free-living wild animals and birds (Palmgren et al, 1997;Čížek et al, 2007;Abulreesh, 2011), domesticated animals (Seepersadsingh & Adesiyun, 2003;Van Immerseel et al, 2004;Ebani et al, 2005), natural waters (fresh and marine) Harakeh et al, 2006), sewage effluents and sludge (Berge et al, 2006;Espigares et al, 2006) and from diarrhea patients (Ling et al, 1998;Graziani et al, 2008) worldwide. In general, a well established link between the use of antibiotics in food-producing animals and drug-resistant salmonellae is described and well understood for food-borne nontyphoidal salmonellae (Mølbak, 2004).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…For the identification of suspected Salmonella isolates, subculture from a single colony pick was used for the agglutination reaction using polyvalent somatic (O) antisera b for Salmonella. 32 Only isolates with a positive result by agglutination test were tentatively confirmed to be Salmonella. The Salmonella isolates were stored at 280uC after subculture on XLD agar for further serotyping and testing of antimicrobial resistance.…”
Section: Cultivation Identification and Serotyping Of Salmonella Ismentioning
confidence: 99%
“…In pet reptiles, limited information has been reported with regard to antimicrobial resistance of Salmonella worldwide. A previous study 32 in Trinidad indicated that 100%, 66.7%, 66.7%, and 33.3% of the Salmonella isolates from reptiles were resistant to streptomycin, cephalothin, neomycin, and gentamycin, respectively. The current study was thus conducted to determine the epidemiological patterns of Salmonella colonization in reptiles collected from various sources in Taiwan.…”
Section: Introductionmentioning
confidence: 99%